Voices of Deficit: Mental Health, Criminal Victimization, and Epistemic Injustice. (January 2017) - Carver, Liddy; Morley, Sharon; Taylor, Paul
People who endure mental and emotional distress experience a plethora of negative experiences beyond the effects of the symptoms themselves. For centuries, the designation of labels of difference; that is, those which transgress approved social norms have affected the lived experiences of those individuals, and more widely in structuring responses, engagements with, and attitudes between society and the individual. Understanding the creation of tainted identities, particularly of those with experience of mental and emotional distress, has been well rehearsed in the sociological literature of the second half of the 20th century. Central to much of this analysis has been to understand the nature of the manufacture of deviant identities, how they are sustained, and the impact of these identities on those who experience them. This article explores the experience of those with mental and emotional distress as a victim of crime. The interconnectedness of matters of identity created though the application of a diagnosis of illness or disorder is addressed as is the crisis of criminal victimization. This is achieved via an exploration of contemporary concerns surrounding victims of crime with experience of mental and emotional distress, including the (further) loss of voice and agency when interfacing with agencies of the state.